Dually modulated photonic crystals enabling high-power high-beam-quality two-dimensional beam scanning lasers - Sakata, Ryoichi (Nat Commun, 2020)
Mechanical-free, high-power, high-beam-quality two-dimensional (2D) beam scanning lasers are in high demand for various applications including sensing systems for smart mobility, object recognition systems, and adaptive illuminations. Here, we propose and demonstrate the concept of dually modulated photonic crystals to realize such lasers, wherein the positions and sizes of the photonic-crystal lattice points are modulated simultaneously. We show using nano-antenna theory that this photonic nanostructure is essential to realize 2D beam scanning lasers with high output power and high beam quality. We also fabricate an on-chip, circuit-driven array of dually modulated photonic-crystal lasers with a 10 × 10 matrix configuration having 100 resolvable points. Our device enables the scanning of laser beams over a wide range of 2D directions in sequence and in parallel, and can be flexibly designed to meet application-specific demands.